Characteristics and outcome in foreign-born vs Sweden-born patients with myocardial infarction. (25th November 2020) - Zwackman, S; Karlsson, J.-E; Sederholm Lawesson, S; Jernberg, T; Leosdottir, M; Eriksson, M; Alfredsson, J
Abstract: Introduction: Immigration is increasing in most European countries. Little is known about differences in baseline characteristics and outcome between foreign-born and native patients with myocardial infarction (MI). Purpose: To investigate differences in baseline characteristics and one-year mortality after an MI, based on region of birth. Methods: We included 194 498 MI patients (36% women) between 2005 and 2016 from the SWEDEHEART registry and compared them according to region of birth: Sweden (Sw, n=166020), Other Nordic countries (No, n=10856), EU countries except Nordic (EU, (n=6301), Non-EU Europe (non EU, n=4779), Asia (n=4927), Africa (n=669), S America (n=567) and N America (n=379). One-year mortality was assessed using a Cox regression model (pairwise with Swedish-born as reference) and in a second model adjusting for age and sex. Data are presented as hazard ratios (HR) with 95% confidence intervals (CI). Results: There was an increased proportion of foreign-born patients over time (12.8 to 16.7%). We observed substantial differences in risk factors and comorbidity according to region of birth (lowest vs highest value) in age (mean) (58 vs 72 year, African vs Sw. born), smoking (19 vs 39%, Sw. vs Asian born), history of diabetes (20 vs 36%, African vs Sw. born), hypertension (40 vs 59%, born in African vs No.), MI (17 vs 23%, S America vs EU born) stroke (9 vs 20%, born in S American vs No.), low income (28% vs 56%, Sw. vs Asian born) and low level of education (27 vs 49%, born in Africa vs No.). One-year mortality according to region of birth was 15.4% for patients born in Sweden, 14.0% for patients born in other Nordic countries, 12.8% in EU, 9.6% for non-EU Europe, 6.3% for Asia, 8.4% for Africa, 6.7% for S America and 15.0% for N America. After adjustment for age and sex, the only significant differences were higher mortality in patients born in other Nordic countries (HR 1.1, 95% CI: 1.01–1.12), non-EU Europe (HR=1.12, 95% CI: 1.02–1.23) and Africa (HR=1.68, 95% CI: 1.29–2.19) compared to patients born in Sweden. Conclusions: We observed increased rate of foreign-born MI patients, with differences in risk profile, comorbidity, education and financial resources according to region of birth, which may impact on observed differences in outcome. Equal access to care pose a challenge which may merit a more comprehensive and individualised approach to cardiac care. Future analyses should explore differences in treatment based on region of birth and potential association with outcome. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): The Kamprad Family for Entrepeneurship, Research and Charity; The County Council of Östergötland, Sweden; Medical Research Council of Southeast Sweden